Low-Dose Decitabine Monotherapy Reverses Mixed Chimerism in Adult Patients After Allogeneic Hematopoietic Stem Cell Transplantation With Myeloablative Conditioning Regimen: A Pilot Phase II Study - Wang, Ling; Wang, Li-ning; Zhou, Ji-fang; Gao, Wen-hui; Jiang, Chuan-he; Tang, Wei; Zhao, Wei-li; Hu, Jiong; Jiang, Jie-ling (Frontiers in Medicine, 2021)
T cell mixed chimerism (MC) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) with myeloablative conditioning for hematological malignancies may indicate engraftment failure or disease relapse. Immune modulation, such as donor lymphocyte infusion (DLI) or the rapid tapering-off or stopping of immunosuppressive treatment, can reverse MC to full donor chimerism (FDC). However, the development or aggravation of graft-versus-host disease (GvHD) and the related mortality remain major concerns with immune modulation. In this prospective, single-arm study (NCT03663751), we tested the efficacy and safety of low-dose decitabine (LD-DAC, 5 mg/m2 daily for 5 days and repeated every 6–8 weeks) without immune modulation in the treatment of patients with MC to prevent MC-associated relapse and/or graft failure. A total of 14 patients were enrolled. All the patients received myeloablative conditioning regimens, and MC was documented from day +30 to day +180 after allo-HSCT with a donor chimerism level ranging from 59 to 97% without detectable measurable residual disease (MRD). Eleven patients (78.6%) responded favorably to treatment, showing increased levels of donor chimerism (≥95%), while nine achieved FDC. All of these patients maintained their responses for a median of 11 months (3–22). The three patients who failed to respond favorably eventually either relapsed or experienced graft failure. All three were alive and in remission at the last follow-up after the second allo-HSCT. LD-DAC monotherapy was well tolerated and exerted limited hematological and nonhematological toxicities. New-onset GvHD symptoms were observed only in two patients. Overall, the estimated 2-year overall survival (OS) and event-free survival (EFS) after allo-HSCT were 90.9 ± 8.7% and 67.0 ± 13.7%, respectively. In conclusion, LD-DAC alone could reverse MC in most patients after allo-HSCT with myeloablative conditioning, while those who achieved FDC enjoyed long-term EFS without major complications. Further prospective studies with larger sample sizes are warranted to confirm the benefits of LD-DAC.